Dual bronchodilatory and pulmonary anti-inflammatory activity of RO5024118, a novel agonist at vasoactive intestinal peptide VPAC(2) receptors - Tannu, SA (Blackwell Science Inc, 2010)
BACKGROUND AND PURPOSE: Vasoactive intestinal peptide is expressed in the respiratory tract and induces its effects via its receptors, VPAC(1) and VPAC(2). RO5024118 is a selective VPAC(2) receptor agonist derived via chemical modification of an earlier VPAC(2) agonist, RO0251553. In the present studies, we characterized the pharmacological activity of RO5024118. EXPERIMENTAL APPROACH: Stability of RO5024118 to human neutrophil elastase was assessed. Bronchodilatory activity of RO5024118 was investigated in guinea pig and human isolated airway smooth muscle preparations and in a guinea pig bronchoconstriction model. Pulmonary anti-inflammatory activity of RO5024118 was investigated in a lipopolysaccharide mouse model and in a porcine pancreatic elastase (PPE) rat model. KEY RESULTS: RO5024118 demonstrated increased stability to neutrophil elastase compared with RO0251553. In human and guinea pig isolated airway preparations, RO5024118 induced bronchodilatory effects comparable with RO0251553 and the long-acting β-agonist salmeterol and was significantly more potent than native vasoactive intestinal peptide and the short-acting β-agonist salbutamol. In 5-HT-induced bronchoconstriction in guinea pigs, RO5024118 exhibited inhibitory activity with similar efficacy as, and longer duration than, RO0251553. In a lipopolysaccharide-mouse model, RO5024118 inhibited neutrophil and CD8(+) cells and myeloperoxidase levels. In rats, intratracheal instillation of PPE induced airway neutrophilia that was resistant to dexamethasone. Pretreatment with RO5024118 significantly inhibited PPE-induced neutrophil accumulation. CONCLUSIONS AND IMPLICATIONS: These results demonstrate that RO5024118 induces dual bronchodilatory and pulmonary anti-inflammatory activity and may be beneficial in treating airway obstructive and inflammatory diseases.